Atrazine Affects the Circadian Rhythm of Microcystis Aeruginosa. (February 2014) - Qian, Haifeng; Wei, Yong; Bao, Guanjun; Huang, Baochen; Fu, Zhengwei
<x xml:space="preserve">Abstract</x> This study provides original data regarding the effects of atrazine (Atr) on the circadian rhythm of the cyanobacterium Microcystis aeruginosa. The results reveal that the circadian rhythms of the central circadian oscillator genes reached their peaks from 1 to 2.5 h after the light was switched on, and the circadian rhythms of physiologically related genes were highly synchronized with the central circadian oscillator genes. These circadian rhythms were consistent with cell growth at the physiological level. The circadian rhythms of the central circadian oscillator genes were altered, and their peaks disappeared or were delayed by the Atr treatment. Therefore, the rhythms of the physiologically related genes in this study also changed to synchronize the new circadian rhythms. And the physiological parameters were tightly correlated with the gene circadian rhythm in the Atr treatment, suggesting that Atr affects M. aeruginosa growth by possibly altering the circadian expression patterns of the clock. Furthermore, this influence is related to the exposure time point of Atr. Thus, chemicals treated in the suitable exposure time point can exert their fullest effects against cell growth